A comparison of training program practiced by equine establishments to compete in 120 km endurance race - Mohd Adzahan, Noraniza; Mohd Zulkaffli, Hazira Filza; Omar, Mohamed Ariff (2012)
Training provides physiological adaptation, resulting increase in fitness of athletics horses, which eventually increase their performance. The primary aim of a training program is to produce the best performing athletic horse with minimal injuries. A survey was conducted using a questionnaire to identify various training programs practiced by the local endurance horse establishments with regards to techniques and duration of the program. Fifteen athletic endurance horses with three horses representing each of the five equine establishments were used in this study. Performance parameters monitored were the average recovery time, average speed, completion rate and level of performance. Kruskal-Wallis test was used to compare conditioning programs practiced by different establishments in relation to their performances. The mean of the average speed of horses from different establishments ranged from 9.30 to 15.20 km hr-1. Stable A that practices all basic endurance conditioning techniques with a training duration of more than 3 months had the highest average speed (15.20 ± 0.05 km hr-1) and the shortest average recovery period (12.28 ± 1.18 min) with 100 % completion rate in 120 km endurance race category. Therefore, the training program practiced by Stable A is suggested to be an optimal training program suited for horses under Malaysian conditions in producing good and competitive endurance horses locally.